Physiological changes in Mexican lemon trees in production infected with HLB - Manzanilla-Ramírez, Miguel Ángel; Villegas-Monter, Ángel; Velázquez-Monreal, José Joaquín; Zavaleta-Mancera, Hilda Araceli; Sandoval-Villa, Manuel; Muñoz-Orozco, Abel (Revista Mexicana de Ciencias Agrícolas, 2019)
Huanglongbing (HLB) is the most devastating citrus disease in the world and has been present in the state of Colima since 2010, the area producing Mexican lemon (Citrus aurantifolia). This disease causes an imbalance in the distribution of carbohydrates and inhibits photosynthesis. It also affects the concentration of nutrients in leaf. The objective of this work was to determine the physiological changes in trees in Mexican lemon production infected with HLB. The study was carried out in Colima in 2017. The concentration of starch, sucrose and glucose was determined in the central leaf veins and sheet of leaves of different ages (120 and 30 days) and root starch. The concentration of chlorophylls by analytical method and SPAD index in leaves with different levels of HLB symptoms and foliar analysis of mineral nutrients. The leaves with HLB had a higher concentration of starch in the 120-day leaf. Sucrose was concentrated in the leaf veins of 120 days. While glucose was increased in the leaf veins of 30 and 120 days. The roots of trees infected with HLB showed 40% lower concentration of starch compared to healthy trees. Decrease in chlorophyll content and SPAD index depending on the degree of involvement. As well as lower concentration of K, Ca, Mg, Cu, Fe, Zn and B. Knowing the changes caused by HLB in Mexican lemon will allow to develop practices that reduce its impact.
Keywords: Citrus aurantifolia; chlorophyll; huanglongbing; sugars